(3JMdjd GdHjGfGJ HGSJNOGe HQfGeL (BMicrosoft Excel 2003 :s (3GdEUOGQGJ ef (BExcel 2000 (3Gdi(BExcel 2003 /s - (3YfGfj, YeQhs ((3GdbGgQI(B: s (3OGQ GdcJH GdYdejI ddfTQ hGdJhRjY(B, s, 2004)
(3JUfja GdHjGfGJ(B- (3GdGSGdjH GdeHOFjI GdeSJNOeI aj JMdjd GdHjGfGJ(B- (3JMdjd GdHjGfGJ aj (BMicrosoft Excel- (3GdJYQa Ydi JbGQjQ GdLOGhd GdeMhQjI hJbGQjQ GdJNWjWGJ GdHjGfjI GdeMhQjI(B- (3JMdjd GdHjGfGJ HGSJNOGe echfGJ hjH dMReI HQGeL (Boffice- (3COhGJ JMdjd GdHjGfGJ aj (BExce.s
Keywords: (3GdHQeLjGJs; (3GdMGSHGJ GdEdcJQhfjIs; (3JMdjd GdHjGfGJs; Microsoft Excel 2003